Product Strategy and Promotion in Creating Brand Awareness and Consumer Loyalty - I Putu Hery Pratama Artha; I GN Putra Suryanatha (Jurnal Manajemen dan Bisnis, 2016)
Globalization is happening in the world today have consequences on the increasinglyfierce competition for a company of any good business field of industry, commerce, banking,service industry, tourism and business sectors. For a financial institution, one of the mostimportant factors to increase customer satisfaction is to provide the best possible service tothe consumer or customer. It shows the importance of customer satisfaction as a referenceand objectives of each company's strategy to always maintain a sustainable manner evenhave to be improved in terms of products, promotions, brand awareness to achieve theexpectations of the consumer. The purpose of this study were: 1) to assess and analyze theeffect of product strategy for brand awareness. 2) to assess and analyze the effect ofpromotions on brand awareness. 3) to assess and analyze the effect of product strategy oncustomer loyalty. 4) to determine and analyze the effect of the promotion effect on customerloyalty. 5) to determine and analyze the effect of brand awareness on consumer loyalty.From analysis and discussion that has diuraaikan can be concluded that 1) the productstrategy and significant positive effect on brand awareness, which means the higher theproduct strategy, the better brand awareness. 2) the promotion of positive and significantimpact on brand awareness, which means that the enhanced promotion of the better brandawareness. 3) the product strategy and significant positive effect on customer loyalty, whichmeans that the enhanced product strategy, the better consumer loyalty. 4) promotion ofpositive and significant impact on customer loyalty, which means that the enhancedpromotion of the better customer loyalty.5) brand awareness and significant positive effect oncustomer, which means that the enhanced brand awareness, the better consumer loyalty.Keywords: product strategy, promotion, brand awareness, consumer loyalty